Capacity, control and responsibility in Parkinson's disease patients with impulse control disorders: Views of neurological and psychiatric experts. (July 2019) - Dawson, Andrew; Michael, Jordie; Dilkes-Frayne, Ella; Hall, Wayne; Dissanayaka, Nadeeka N.; Carter, Adrian
Abstract: Dopamine replacement therapy can induce impulse control disorders (ICDs) (e.g., hypersexuality) in susceptible Parkinson's disease patients. ICDs can sometimes result in criminal offending. In a number of past Commonwealth cases, it appears offending ICD patients have been considered to be suffering from 'irresistible impulses' such that their decision-making capacity, behavioural control and responsibility were totally compromised. This contrasts with courts' general scepticism of drug-induced 'compulsion' in cases of addiction-related offending. In one case of explicit ICD-related offending, testimony was limited to three experts and not contested by the prosecution. We explored whether the testimony offered in this particular case, and another similar case, reflects the views of the neurological and psychiatric communities at large. Thematic analysis revealed that neurologists, geriatricians and psychiatrists ( n = 11): (a) attributed ICDs to a variety of causes; (b) considered ICD patients' decision-making capacities and behavioural control to be partially, but not totally, compromised; (c) were divided or ambivalent about ICD patients' responsibility; and (d) astutely noted the difficulties inherent in assessing complex constructs such as 'control' and 'responsibility'. We suggest that there is sufficient divergence between our findings and expert testimony from past cases for prosecution teams to engage their own experts in future cases of ICD-related offending.